Differential Functional Changes of Nav1.2 Channel Causing SCN2A-Related Epilepsy and Status Epilepticus During Slow Sleep - Miao, Pu; Tang, Siyang; Ye, Jia; Tang, Jihong; Wang, Jianda; Zheng, Chaoguang; Li, Yuezhou; Feng, Jianhua (Frontiers in Neurology, 2021)
Background: Nav1.2 encoded by the SCN2A gene is a brain-expressed voltage-gated sodium channel known to be associated with neurodevelopment disorders ranging from benign familial neonatal infantile seizures(BFIS) to developmental and epileptic encephalopathy(DEE) and autism spectrum disorder. Interestingly, status epilepticus during slow sleep (ESES), which aggravates cognitive impairment, has been found in SCN2A related epilepsy. However, the functional features and the relationship between SCN2A and ESES have not been researched. Method: We herein investigated the functional consequences of an unpublished de novo V911A and the other two other published variants in patients with SCN2A related disorder and ESES by whole-cell patch-clamp studies in transfected HEK293T cells. Results: The unpublished V911A and published K1933M variants detected in patients with DEE exhibited a profound gain-of-functional(GOF) change. Another published benign familial neonatal infantile seizures (BFIS) variant S863F significantly reduced current density as a loss of functional (LOF) change. The refractory epilepsy in the patient with V911A was controlled by using the precise treatment of oxcarbazepine (OXC) since the age of 3 months. ESES was found at 18 months during the seizure-free period. We finally chose an aggressive treatment for eliminating ESES by using methylprednisolone combined with levetiracetam and nitrazepam instead of the precise treatment of OXC. Conclusion: Both GOF and LOF variants in the SCN2A gene can lead to ESES among the phenotypes of DEE and BFIS. We should monitor the electroencephalogram regularly in the patients with SCN2A related epilepsy even during their seizure-free period.